View from the pass : Friends of Raton Anthropology - Ames, Neil (Raton, New Mexico Raton Range, 1975)
Newspaper Article on Mrs Robertson and the friends of Raton Anthropology. The group that studies the area anthropology.
Master list item #: 17
File location is in the Raton File Cabinet
Keywords: Robertson, Gordon (Mrs.); Taylor, Morris; Friends of Raton Anthropology; Raton Bicentennial Committee; Philmont Museum; Arthur Johnson Memorial Library; Trinidad Junior College; Local History; Biography; Life and Customs; Anthropology; Indian Tribes -- Jicarilla Apache -- Pueblo Indian -- Kiowa -- Camanche -- Cheyenne -- Arapahoe; Eghnology; Petroglyphs; Archaeologic; Indians -- Basket Making; Arrowheads; Transportation; Exhibits; Raton, New Mexico; Fort Union; Cimarron, New Mexico; Trinidad, Colorado